Combined Use of Metoclopramide and Glycopyrrolate as A Prophylactic Antiemetic in Elective Cesarean Section Under Spinal Anesthesia - Dinesh Thakur; Mihir Goswami; Himanshu Shah (Medsci Publications, 2011)
Objective: To compare the combined effect of two traditional antiemetic drugs (metoclopramide and glycopyrrolate) against published data of effect of single antiemetic drug for prevention of nausea and vomiting in women undergoing lower section caesarean section under spinal anaesthesia Methods: Seventy eight full term parturient women undergoing lower segment cesarean section under spinal anesthesia(using 5% lignocaine) were injected metoclopramide 10mg & glycopyrrolate 0.2mg intravenously at the time of abdominal incision. The frequency of nausea and vomiting and Apgar scores of neonates were noted. Results: Incidence of nausea was noted in 3.84% during operative and post operative period. No incidence of vomiting and any other adverse effects were observed. Apgar scores were >8 in all neonates at one and five minutes. Conclusion: Incidence of vomiting is low (zero case) in current study group compared to groups(data from published research) with either metoclopramide or glycopyrrolate or ondansetron but observed differences are statistically insignificant, however the upper class interval limit of Z value falling above significance level (>1.96) in all groups suggesting that it might significant and required further studies to prove or disprove significantly lower incidences of nausea and vomiting if combine use of two drugs (glycopyrrolate plus metoclopramide) as a prophylactic antiemetic in elective cesarean section under spinal anesthesia.